Potrošniška prodajna pogodba in pogodba o dobavi digitalne vsebine in digitalnih storitev - Možina, Damjan (Pravni letopis, 2023)
The Slovenian legislator has transposed the content of Directives 2019/770 on digital content and digital services and 2019/771 on consumer sales of goods into the revised Consumer Protection Act, each within its set of extensive provisions. Both directives provide the criteria for conformity with the contract and the remedies of the consumer in case of non-conformity. In terms of basic structure, they build upon the previously applicable Directive 99/44 on consumer sales but introduce a variety of novelties. The paper presents the system of remedies for non-conformity with the contract (i.e. performance with material or legal defects). The regulation of contracts for the supply of digital content and services represents a refreshment of consume contract law in the light of technological development. The author notes that the transposition of directives into Slovenian law was not well-prepared. In addition to errors in the transposition, the author is critical with regard to some decisions of the legislator on the options provided by the directive, overlooked connections with the Obligations Code, as well as ambiguities, lack of transparency, and a low level of the Slovenian language in the legislative text.
Keywords: digitalne storitve; digitalne vsebine; direktive; obligacijsko pravo; potrošniško pravo; pravna napaka; prodajne pogodbe; stvarna napaka; varstvo potrošnikov